2014
DOI: 10.1007/s12185-014-1521-2
|View full text |Cite
|
Sign up to set email alerts
|

From empiric to mechanism-based therapy for peripheral T cell lymphoma

Abstract: Peripheral T cell lymphoma (PTCL) represents a heterogeneous group of mature T and natural killer cell-derived neoplasms, comprising approximately 10 % of non-Hodgkin lymphoma. Although at least 20 distinct histologic subtypes of PTCL have been identified, the historical treatment approach has been uniform application of anthracycline-based combination chemotherapy, resulting in significantly inferior outcomes compared to B-cell non-Hodgkin lymphoma. Because of the generally poor outcomes with conventional che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 115 publications
0
18
0
Order By: Relevance
“…Some studies have recently described the efficacy of ALK inhibition in ALCL, both in murine models [40] and in preliminary clinical studies: in one trial 2 ALK+ ALCL patients reported complete remission of the disease within 1 month of treatment with Crizotinib, the response being sustained 5–6 months later [8]. A later clinical trial with 9 ALK+ ALCL patients treated with Crizotinib showed an objective response rate of 100%, a complete remission rate of 100%, a median duration of response of 10 months and 3-year progression-free survival of 63% with a plateau in the curve after 6 months [9]. In fact, Crizotinib has been approved by the FDA for the treatment of ALK+ non-small cell lung cancer [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have recently described the efficacy of ALK inhibition in ALCL, both in murine models [40] and in preliminary clinical studies: in one trial 2 ALK+ ALCL patients reported complete remission of the disease within 1 month of treatment with Crizotinib, the response being sustained 5–6 months later [8]. A later clinical trial with 9 ALK+ ALCL patients treated with Crizotinib showed an objective response rate of 100%, a complete remission rate of 100%, a median duration of response of 10 months and 3-year progression-free survival of 63% with a plateau in the curve after 6 months [9]. In fact, Crizotinib has been approved by the FDA for the treatment of ALK+ non-small cell lung cancer [3].…”
Section: Discussionmentioning
confidence: 99%
“…Although different histological subtypes of PTCL have been identified, the treatment approach has been essentially based on the application of anthracycline-based combination chemotherapy, resulting in poor outcomes [9]. To date, only 3 agents have been recently approved by the FDA for the treatment of relapsed or refractory PTCL: pralatrexate, romidepsin and brentuximab vedotin [9], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-anaplastic peripheral T cell lymphoma (PTCL) is a heterogeneous group of diseases that accounts for 0.9-1.8 % of all childhood non-Hodgkin's lymphoma (NHL) [1][2][3][4][5]. In the 2008 World Health Organization (WHO) classification, PTCL comprised 21 subtypes, including a leukemic/disseminated group, an extranodal group, a cutaneous lymphoma group, and a nodal group [6].…”
Section: Introductionmentioning
confidence: 99%
“…Overall response rate [ORR, CR plus PR (partial remission)] was 60 % (CR 2 cases, PR 4 cases and 1 case omitted because of no description). ORR with R-CHOP and R-CHOP-like regimens was 75 %, which was slightly inferior to 79 through 84 % of ORR in CD20-negative PTCL-NOS treated with CHOP or CHOP-like regimens [30]. More scrutinizing the relationship between the intensity of CD20 immunostaining and the efficacy of rituximab-based chemotherapy, we found that ORR was 100 % in cases in strong staining (n = 3), while 33.3 % in cases in variable staining (n = 6).…”
Section: Discussionmentioning
confidence: 77%